Predictors of Cerebral Arteriovenous Malformation Mortality: A Single-center, Five-year Retrospective Study - Patricio Garcia-Espinosa; Edgar Botello-Hernández; Gabriela Torres-Hernández; Clarissa Guerrero-Cavazos; Estefania Villareal-Garza; Andrea Flores-Rodriguez (University Library System, University of Pittsburgh, 2021)
Background: Arteriovenous Malformations (AVMs) are abnormalities in intracranial vessels between the arterial and venous systems. This study aimed to identify the predictors of mortality in patients that presented to our hospital with AVMs, ruptured or unruptured, and correlate them to those available in the literature. Methods: An analytical, observational, retrospective study was performed to review data of patients with cerebral AVMs in the University Hospital "Dr José Eleuterio González" from January 2016 to December 2020. Clinical files were reviewed based on AVMs diagnosis according to the  International Classification of Diseases 10th Revision, ICD-10. Variables were subjected to a univariate analysis and those found significant (p-value < 0.05) were subjected to a logistic regression. Results: A total of 80 patients were included in our study. Most of the participants were females (56.3%) and three were pregnant. The most common presenting symptom was holocranial headache (34 cases) occurring between the hours of 22:00 to 7:00. The most significant predictors of mortality were a total bleeding volume greater than 9.18 cm3 (p = 0.010), the presence of more than one symptom (p = 0.041), and a history of previous cerebral intraparenchymal hemorrhage (p = 0.014). Conclusion: Results demonstrated an important association between intracranial bleeding and mortality. Ultimately, more prospective studies are needed to determine predictor factors for mortality in AVMs patients.